2016
DOI: 10.3892/br.2016.678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Sijunzi decoction on the immunological function in rats with dextran sulfate-induced ulcerative colitis

Abstract: Abstract. The present study investigated the effects of the Sijunzi decoction (SJZD) at various dosages on the immunological function of rats with 3% dextran sulfate sodium (DSS; molecular weight 5,000)-induced ulcerative colitis (UC). A total of 40 male Wistar rats were randomly divided into 5 groups: Normal, model, low-dose SJZD, moderate-dose SJZD and high-dose SJZD groups. The 3% DSS was intragastrically administered for 7 consecutive days in order to induce the UC model. The normal group consumed distille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, no significant side-effects such as body-weight loss or pathological change in lung tissues were observed. A recent study also used a high level dosage of a similar decoction with 30.0 g/kg for rats which is equal to about 45 g/kg for mice, whereas no distinct toxicity and side effects were observed (Yu et al, 2016). However, toxicity or side effects of MSJZT are still not fully understood, and further studies are needed to assess toxicity of MSJZT.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant side-effects such as body-weight loss or pathological change in lung tissues were observed. A recent study also used a high level dosage of a similar decoction with 30.0 g/kg for rats which is equal to about 45 g/kg for mice, whereas no distinct toxicity and side effects were observed (Yu et al, 2016). However, toxicity or side effects of MSJZT are still not fully understood, and further studies are needed to assess toxicity of MSJZT.…”
Section: Discussionmentioning
confidence: 99%
“…JQD was invented based on this principle: Codonopsis pilosula and radix Astragali could nourish the qi, Portulacaceae and Radix sanguisorbae could clear heat and dampness, and Panax notoginseng and Tuber Bletilla striata could promote blood circulation by removing blood stasis. [ 23 , 24 ] Modern studies have found that Astragalus membranaceus (Fisch.) Bunge containing Astragalus polysaccharide had a beneficial immune regulatory effect on experimental colitis, which promoted the expression of T helper cell 1 (Th1) and T helper cell 2 (Th2)-specific transcription factors, but ultimately led to a shift toward the Th2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The colon length was measured by using a ruler. The colon was observed and the colonic mucosal damage index (CMDI) was scored [ 25 ]. The scoring method was as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%